(untitled) (International journal of artificial intelligence, 2026)
The article notes that in the Navoi region, the Sarmyshsay gorge, which has preserved 7 thousand years of history, contains more than 10 thousand unique stone inscriptions, described landscapes, places and settlements of the Stone Age, remains of ancient tombs and irrigation networks, ruins of an ancient village, the charming nature of the gorge, its study of natural and cultural heritage